Uso del Chat GPT como apoyo en el aprendizaje de la unidad 1: Los Orígenes para los estudiantes de octavo año de EGB - Tenelema Muñoz, Dennys David (2025)
The researcher conducted the current work due to the limited use of existing technological tools within the educational environment for topics that require extensive academic adaptation. For this reason, it was vital to propose a teaching guide as a resource to contribute to the teaching and learning of Unit 1: The Origins, which is part of the social studies subject, with eighth-year general basic education students at the PCI Chimborazo Educational Unit. The research methodology employed a quantitative approach with a non-experimental design, descriptive level, basic object, field location, and bibliographic references. The study required data collection through a survey and questionnaire, with a study population of 15 students. As a result, the researcher found that students agreed with the resources, activities, games, reviews, and evaluations presented in the teaching guide, which focused on the use of GPT Chat with different prompts that are very helpful in addressing the doubts that each student has during learning. Through social media, it was possible to conclude that the topics covered in Unit 1, "The Origins," were well accepted by students. The content presented was of high quality and engaging, promoting participation, motivation to acquire knowledge, incentives for studying, educational dynamics, collaboration, and teamwork. It ensured that the students used the teaching guide to enhance their understanding of social studies.